Endosymbiotic Bacteria Associated with Aphis gossypii Glover (Hemiptera:Aphidae) infesting taro - B. G., Sangeetha; E. V., Sreejitha; C. A., Jayaprakas; E. R., Harish (JOURNAL OF ROOT CROPS, 2019)
Aphids are one of the important sucking pests of many agriculturally important crops, associated with a wide variety of bacterial endosymbionts that confer many ecologically relevant traits to the host insect. Endosymbiotic bacteria (ESB) play a vital role even in the physiology of the host, hence identification of ESB associated with the aphids will help to develop important strategies for the management of this noxious pest. In the present study molecular characterization of ESB associated with the aphid, Aphis gossypii infesting taro was done. Morphological characters of the four strains revealed that each isolate has different colony characters. Further, the genomic DNA was isolated from each of the EPB isolates and PCR amplification of 16S rRNA gene was carried out using universal primers. The 16S rDNA gene sequences of endosymbiotic bacterial isolates were generated by sequencing the PCR product and were aligned with each other by using BioEDIT software. The nucleotide sequences were compared with those in the NCBI databases using the Basic Local Alignment Search and four genus viz., Bacillus, Pesudomonas, Pantoea and Staphylococcus were confirmed. From the aligned sequences phylogenetic tree was constructed by the Neighbor-Joining method using MEGA version X.